(untitled) (Sociologisk Forskning, 1995)
Civil society - Object of sociology or concept in politics? This paper starts by investigating the different meanings and usages of the concept of ”civil society.” An overview singles out the two dominant perspectives in current discussions: the neoliberal and the neomarxist perspectives. Thereafter, the paper examines what sociologists mean when claiming that civil society is the object of sociological thought. A third perspective emerges here, namely civil society as the sphere in which social integration takes place. Attention is then turned to some critical remarks recently raised against the concept by Swedish sociologists, critizing it for being highly ambiguous and lacking analytical dimensions. This paper argues that this critique is misleading - it totally ignores the meaning of the concept put forward in the neomarxist perspective. I conclude that despite the fact that some of the meanings applied to the concept can be characerized a sun-sociological, there are other meanings that fit very well with sociological thought.